The potential of sector coupling in future European energy systems: Soft linking between the Dispa-SET and JRC-EU-TIMES models - Pavičević, Matija; Mangipinto, Andrea; Nijs, Wouter; Lombardi, Francesco; Kavvadias, Konstantinos; Jiménez-Navarro, Juan-Pablo; Colombo, Emanuela; Quoilin, Sylvain (Elsevier, 2020)
The relevance of sector coupling is increasing when shifting from the current highly centralised and mainly fossil fuel-based energy system to a more decentralized and renewable energy system. Cross-sectoral linkages are already recognized as a cost-effective decarbonisation strategy that provides significant flexibility to the system. Modelling such cross-sectoral interconnections is thus highly relevant. In this work, these interactions are considered in a long-term perspective by uni-directional soft-linking of two models: JRC-EU-TIMES, a long term planning multisectoral model, and Dispa-SET, a unit commitment and optimal dispatch model covering multiple energy sectors such as power, heating & cooling, transportation etc. The impact of sector coupling in future Europe-wide energy systems with high shares of renewables is evaluated through five scenarios. Results show that the contributions of individual sectors are quite diverse. The transport sector provides the highest flexibility potential in terms of power curtailment, load shedding, congestion in the interconnection lines and resulting greenhouse gas emissions reduction. Nevertheless, allowing combinations of multiple flexibility options such as hydro for the long-term, electric vehicles and flexible thermal units for the short-term provides the best solution in terms of system adequacy, greenhouse gas emissions and operational costs.
Keywords: Recursos energéticos - Europa; Desarrollo sostenible; Dispa-SET; Sector coupling; High RES Europe; Electric vehicles; Thermal storage; Hydropower